2017
DOI: 10.1515/ouacsce-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermal discomfort indices for the coastal zone of Black Sea, in Dobrogea Region

Abstract: The main goal of this paper is to establish the thermal comfort or thermal discomfort conditions for the coastal zone of Black Sea, in Dobrogea region (Romania). In the last century there have been many efforts to assess the degree of thermal discomfort and heat stress for different types of climates and taking into account as many climate variables. The thermal discomfort is difficult to be quantified because it is necessary to consider a range of environmental and human factors to decide what makes a person … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study uses three healthy subjects that consist of all males. The statistics from the Department of Statistics Malaysia mentioned that for the year 2018, there are 1.3 million of workers in the construction industry and 2.2 million of workers in the manufacturing industry [27]. It can be concluded that majority of the workers in the construction industry work at the construction site rather than in an indoor office and there are many workers in manufacturing industry who work in a hot environment.…”
Section: Methodology 21 Subjectmentioning
confidence: 99%
“…This study uses three healthy subjects that consist of all males. The statistics from the Department of Statistics Malaysia mentioned that for the year 2018, there are 1.3 million of workers in the construction industry and 2.2 million of workers in the manufacturing industry [27]. It can be concluded that majority of the workers in the construction industry work at the construction site rather than in an indoor office and there are many workers in manufacturing industry who work in a hot environment.…”
Section: Methodology 21 Subjectmentioning
confidence: 99%
“…Since SET is independent from the environment, it is suitable for most meteorological conditions [13,15]. Most of the outdoor thermal indexes use physical factors (clothing insulation, metabolic activity, skin temperature, and body composition), as pointed out [19] and employ four environmental parameters, air temperature, mean radiant temperature (T mr ), air velocity, and relative humidity [20]. Those environmental parameters play an essential role in the definition of the thermal comfort of citizens; therefore, their variation allows to understand their mutual and combing impacts on the microclimate [21].…”
Section: Introductionmentioning
confidence: 99%